EFEKTIVITAS PENDAFTARAN DAN PENGELOLAAN SISTEM INFORMASI ORGANISASI KEMASYARAKATAN KOTA PEKANBARU TAHUN 2021-2023 - Nst, Asiatunnur; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Effectiveness is the level of success of an activity, program, or policy in achieving the goals and objectives that have been previously set. Something is said to be effective if the results achieved are in accordance with or close to the planned targets, in terms of quality, quantity, and time. The Community Organization Information System of Pekanbaru City (SIOMANTAP) is one of the new innovations to accelerate the registration of community organizations (ormas) in Pekanbaru City. This research uses Duncan's Theory, which emphasizes aspects of adaptation, integration, and goal achievement in a system. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation studies. The data were analyzed using Duncan's theory of organizational effectiveness, which includes three main aspects: system adaptation to user needs, system integration with other policies and services, and achievement of the main goals of the Ormas data system. The results of the study show that although the SIOMANTAP system has provided convenience in the online registration of community organizations, its effectiveness still faces various obstacles. First, in the aspect of goal achievement, the main goal of the SIOMANTAP system is to increase efficiency and transparency in Ormas management. Although it has provided several benefits such as ease of access to information, the system still needs stability improvements, service mechanism repairs, and evaluations of obstacles faced by Ormas. Second, the aspect of system integration still has limitations in integration between Kesbangpol and Ormas. Many Ormas complain about the lack of admin response and the lack of clarity regarding registration status. Third, the aspect of system adaptation has not fully adapted to the needs of all Ormas. This is evident from user difficulties who are not familiar with technology. A more user-friendly system is needed, as well as training and assistance for Ormas that have difficulty using digital systems. Keywords: Effectiveness, Management, SIOMANTAP